Piperine: An Anticancer and Senostatic Drug - Jae Sung Lim (Frontiers in Bioscience-Landmark, 2022)
Background: Cancer is a representative geriatric disease closely related to senescent cells and cell aging in tissues. Senescent cells that surround cancer tissues reduce the effects of various cancer treatments and induce cancer recurrence through senescence-associated secretory phenotype (SASP) secretion. Thus, for good therapeutic effect, candidate drugs should be selective for both cancer and senescent cells. In this study, we investigated the selective effect of piperine as a potential senostatic agent as well as an anticancer drug. Methods: The effect of piperine on cytotoxicity and cell proliferation was tested by lactate dehydrogenase (LDH) or water-soluble tetrazolium salt (WST) assay. The levels of p16INK4a and p21, mitogen-activated protein kinases (MAPKs), and mammalian target of rapamycin (mTOR) were analyzed by Western blot analysis. The rejuvenation effects of piperine on the senescent cells were investigated by senescence-associated beta-galactosidase (SA-β-Gal) stain, mitochondria membrane potential (MMP) and reactive oxygen species (ROS) levels, and senescence-associated secretory phenotype (SASP) secretion after treatment with piperine in senescent cells. Results: While piperine induced high cytotoxicity in various cancer cell lines, it led to proliferating of premature senescent cells similar with nicotinamide (NA), which is known as a rejuvenating drug of senescent cells. Piperine differently affected cancer cells and premature senescent cells due to the different responses of intracellular signaling pathways and also reversed premature senescence phenotypes and modulated SASP secretion in premature senescent cells. Conclusions: From these results, we propose piperine as an effective cancer treatment that can simultaneously induce senostatic effects and the removal of cancer cells, not as an adjuvant to the existing senostatics for cancer treatment.